Special aspects of movement activity of secondary general school pupils at 15–17 years of age in their spare time - Мандюк, Андрій (Slobozhanskyi Herald of Science and Sport, 2017)
Andriy Mandyuk Purpose: to determine the characteristics movement activity, which is carried out secondary general school pupils at 15–17 years of age in their spare time. Material & Methods study involved secondary general school pupils of 10–11 classes in Lviv, Ternopil, Ivano-Frankivsk and Khmelnytsky. The total number of students was 926 people, which is 6% of the total population. The study used such methods: analysis and synthesis, analysis of scientific and methodological literature, sociological survey Results: specificity of motor activity in spare time is determined, which is carried out by pupils of senior school age. Defined amount of daily and weekly movement activity, as well as the main priorities in the choice of forms and types of movement activity. Conclusion: results of the study will be used to develop a model for optimizing the movement activity of secondary general school pupils at 15–17 years of age using the appropriate forms of movement activity, which is carried out in their spare time.